2017
DOI: 10.1007/s13197-017-2862-7
|View full text |Cite
|
Sign up to set email alerts
|

Carbonated water as a novel washing medium for mackerel (Auxis thazard) surimi production

Abstract: Effect of cold carbonated water (CW) washing on the biochemical properties and gel characteristics of mackerel surimi was evaluated. Three washing cycles were performed with different orders of washing medium including T1 (water, water and water), T2 (CW, water and water), T3 (CW, CW and water) and T4 (CW, CW and CW). The results showed that CW washing, especially T4, caused the decrease in pH, Ca-ATPase activity and surface hydrophobicity and led to the increase in reactive sulfhydryl content. Regardless of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…The scanning electron microscope (SEM) (Gem-iniSEM, Carl Ziess Microscopy, Germany) was used for microstructure analysis (Somjid et al, 2017). Samples with a thickness of 2-3 mm were fixed with 2.5 mL 100 mL −1 glutaraldehyde in 0.2 mol L −1 phosphate buffer (pH 7.2) for 2 h. The samples were then rinsed for 1 h in distilled water before being dehydrated in ethanol with serial concentrations of 50, 70, 80, 90 and 100 mL 100 mL −1 .…”
Section: Microstructurementioning
confidence: 99%
“…The scanning electron microscope (SEM) (Gem-iniSEM, Carl Ziess Microscopy, Germany) was used for microstructure analysis (Somjid et al, 2017). Samples with a thickness of 2-3 mm were fixed with 2.5 mL 100 mL −1 glutaraldehyde in 0.2 mol L −1 phosphate buffer (pH 7.2) for 2 h. The samples were then rinsed for 1 h in distilled water before being dehydrated in ethanol with serial concentrations of 50, 70, 80, 90 and 100 mL 100 mL −1 .…”
Section: Microstructurementioning
confidence: 99%
“…2c). Myoglobin as a member of sarcoplasmic proteins can be leached out from the muscle during washing with water (Somjid et al ., 2017). By increasing the ionic strength and altering the pH in the washing medium (in some cases), the removal efficacy of myoglobin seemed to be improved significantly.…”
Section: Resultsmentioning
confidence: 99%
“…The pH, Ca 2+ -ATPase activity, SH content, protein surface hydrophobicity, and TCA-soluble peptides were determined using the standard methods as described by Somjid et al [9].…”
Section: Determination Of Bio-physico-chemical Properties Of Unwashed Mince and Surimimentioning
confidence: 99%
“…As a result, there is a need for environmentally friendly surimi production with fewer washing cycles, not only to avoid pollution, but also to increase yield and minimize wash water content. Several studies have reported the use of washing solutions such as tap water [6], sodium chloride [7], sodium bicarbonate [8], carbonated water [9], and ozonized water [10] for mackerel surimi production. All of the above-mentioned washing media have been shown to improve quality parameters, but the results differ depending on the fish species.…”
Section: Introductionmentioning
confidence: 99%